Chlorophyll fluorescence is a potential indicator to measure photochemical efficiency in early to late soybean maturity groups under changing day lengths and temperatures - Mathur, Sonal; Seo, Beomseok; Jajoo, Anjana; Reddy, Kambham Raja; Reddy, Vangimalla R. (Frontiers in Plant Science, 2023)
In this study, we employed chlorophyll a fluorescence technique, to indicate plant health and status in response to changing day lengths (photoperiods) and temperatures in soybean early and late maturity groups. Experiments were performed for three-day lengths (12.5,13.5,14.5 hour) and five temperatures (22/14, 26/18, 30/22, 34/26, and 40/32 o C), respectively. Chlorophyll a fluorescence study was conducted in the soybean maturity groups to indicate changes in light reactions of photosystem II. The I-P phase declined for changing day lengths. Active reaction centers decreased at long day length for maturity group III. We observed that low temperature impacted the acceptor side of photosystem II and partially impacted electron transport towards the photosystem I end electron acceptor. Results emphasized that higher temperature (40/32 o C) triggered damage at the oxygen-evolving complex and decreased electron transport and photosynthesis. We studied specific leaf areas and above-ground mass. Above-ground parameters were consistent with the fluorescence study. Chlorophyll a fluorescence can be used as a potential technique for highthroughput phenotyping methods. The traits selected in the study proved to be possible indicators to provide information on the health status of various maturity groups under changing temperatures and day lengths. These traits can also be deciding criteria for breeding programs to develop inbreed soybean lines for stress tolerance and sensitivity based on latitudinal variations.